Why Mark Wrote a Gospel: Taking Another Look. Issue 1 (January 2016) - Wallis, Ian
Abstract : At a time when the cult of Christ was becoming increasingly detached from its historical roots in the ministry of Jesus, Mark, in a stroke of genius, reconnects them. By gathering together memories associated with Jesus, some of which already existed in collections, and forming them into a narrative, the Evangelist introduces Jesus by means of his way of faith and kingdom programme – postponing evaluations of his theological significance until after the crucifixion. What is more, by concluding the Gospel with an invitation to encounter the risen Jesus back where the journey began, faith is once more rooted in his ministry, finding expression through practising his way.